2020
DOI: 10.3390/cancers12030596
|View full text |Cite
|
Sign up to set email alerts
|

VE1 Immunohistochemistry Improves the Limit of Genotyping for Detecting BRAFV600E Mutation in Papillary Thyroid Cancer

Abstract: Detection of BRAFV600E is useful for making diagnosis and risk stratification of papillary thyroid carcinoma (PTC). Molecular testing, however, is not always available for routine clinical use. To assess the clinical utility and reliability of VE1 immunohistochemistry (IHC) for detecting BRAFV600E mutation in PTC, VE1 IHC was performed on the tissue microarrays of 514 patients with PTC and was compared with Sanger sequencing results. Of 514 PTC cases, 433 (84.2%) were positive for VE1 expression. Among 6 disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 53 publications
0
31
0
Order By: Relevance
“…The rate of BRAF V600E mutation in PTC patients mostly depends on the target population and clinicopathological characteristics, including gender, age, tumor stage, tumor focality, lymphovascular invasions, and extrathyroidal extensions 8 . The mutation is found in approximately 50% of PTC cases among western series descended from the USA 9,10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of BRAF V600E mutation in PTC patients mostly depends on the target population and clinicopathological characteristics, including gender, age, tumor stage, tumor focality, lymphovascular invasions, and extrathyroidal extensions 8 . The mutation is found in approximately 50% of PTC cases among western series descended from the USA 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been reported on the performance of VE1 IHC technique to detect the BRAF V600E mutation, and most of these reports showed exceptional concordance between this method and molecular genotyping, thus IHC can be used as an alternative method to Sanger sequencing 1,26,27 . The IHC technique consumes less time to perform multiple tests as compared to molecular methods, consequently decreasing the turnaround time 8 …”
Section: Introductionmentioning
confidence: 99%
“…We enrolled 511 patients who underwent surgery for PTC from January 2008 to December 2010. The present study was performed on the same cohort used in our previous studies [ 34 , 35 , 36 , 37 ]. However, the number of patients was different because tissue loss inevitably occurs during sectioning and staining of the same archival tissue blocks.…”
Section: Methodsmentioning
confidence: 99%
“…PCR reaction was performed using BRAF exon 15-specific primers (forward 5′-TCATAATGCTTGCTCTGATAGGA-3′ and reverse 5′-GGCCAAAAATTTAATCAGTGGA-3′). Bidirectional sequencing was performed using the same primers and BigDye Terminator sequencing kit (Applied Biosystems, Foster City, CA, USA; No.4337457 on a 3730xl DNA analyzer (Applied Biosystems)), as previously described [ 34 , 36 , 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…TNM (Tumor-Node-Metastasis) staging was done according to the 8th edition of the AJCC cancer staging manual [38]. The same data set was used in our previous studies [8,43,44], but clinical follow-up data were updated as of March 2020. All patients with total thyroidectomy took levothyroxine for suppression of thyroid-stimulating hormone (TSH).…”
Section: Patientsmentioning
confidence: 99%